2023
DOI: 10.3390/su15118928
|View full text |Cite
|
Sign up to set email alerts
|

Green Infrastructure as an Effective Tool for Urban Adaptation—Solutions from a Big City in a Postindustrial Region

Abstract: Adaptation to climate change is becoming one of the main paradigms for how cities function and develop. The significant role of green infrastructure (GI) as a tool for cities to adapt to climate change is increasingly emphasized among practitioners of spatial planning and in the research literature. Thus, despite the local impact, green infrastructure planning necessitates the creation of a holistic and integrated city management system. The aim of the article is to identify the effects generated by projects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Faced with the above, a permeable interlocking concrete paving system with the capacity to collect and store rainwater could be used to irrigate green areas, thus allowing the formation of ecosystems that contribute to the production of photosynthesis, thereby resulting in mitigation actions against climate change and, consequently, contributing to a reduction in the generation of greenhouse gases [46,47]. It is also possible to mention that it is an engineering solution that prevents the formation of waterlogging and drainage problems [4,48,49]. The information above is denoted in the balance for a water-sensitive urban design presented in Figure 8.…”
Section: New Sustainable Approaches To the Urban Management Of Stormw...mentioning
confidence: 99%
See 1 more Smart Citation
“…Faced with the above, a permeable interlocking concrete paving system with the capacity to collect and store rainwater could be used to irrigate green areas, thus allowing the formation of ecosystems that contribute to the production of photosynthesis, thereby resulting in mitigation actions against climate change and, consequently, contributing to a reduction in the generation of greenhouse gases [46,47]. It is also possible to mention that it is an engineering solution that prevents the formation of waterlogging and drainage problems [4,48,49]. The information above is denoted in the balance for a water-sensitive urban design presented in Figure 8.…”
Section: New Sustainable Approaches To the Urban Management Of Stormw...mentioning
confidence: 99%
“…Both in Chile and many countries around the world, there is increasing urban growth, where the urbanization of natural basins causes an alteration of their corresponding hydrological processes [1][2][3]. These basins, which are subject to constant urbanization, present more rapid flooding, making the consequences of flooding increasingly severe; presenting a lack of sustainable urban rainwater management systems in which extreme hydrometeorological events test the performance of urban drainage systems; and causing countries to demand new solutions to adapt to climate change [4][5][6].…”
Section: Introduction 1urban Context Of Stormwater Management Conside...mentioning
confidence: 99%
“…Research has demonstrated that urban river corridors, as blue-green infrastructure, perform a dual role as natural and social corridors, thereby contributing significantly to urban stability, comfort, and sustainability (Janiszek & Krzysztofik, 2023;Ji et al, 2012). On the one hand, urban river corridors act as ecological corridors, facilitating the migration of organisms, enhancing biodiversity, and providing habitats and migration routes for wildlife (Baschak & Brown, 1995;Bennett & Mulongoy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…River corridors, known as "blue-green infrastructure", are vital to the stability, comfort, and sustainability of urban areas [4,5]. Firstly, functioning as natural systems within cities, they regulate the urban microclimate, mitigate the urban heat island effect, maintain water and soil, purify water bodies, and enhance biodiversity by creating buffer zones of riverbank vegetation [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%